Reduction of Acute Anterior Shoulder Dislocation Using Intraarticular Lidocaine(IAL) and Stimson’s Technique - Thapa, BB; Chand, P; Kayastha, N; Rana, S; KC, NB; Joshi, A; Singh, BP; Shah, BC; KC, BR (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Shoulder dislocation is common injury requiring urgent reduction. For the reason that patient is not nill orally and anesthetists are not available, reduction under intra venous anaesthesia is not possible. This study was aimed to evaluate the effectiveness of intraarticular lidocaine and stimson’s technique of shoulder dislocation, which could be performed without anesthetist and irrespective of nill orally status. Methods: A prospective observational study was performed from December 2009 to December 2010. Under all antiseptic precautions 20 ml of Lidocaine was injected intraarticularly and reduction was performed by Stimson’s technique. Visual Analogue Score, time for reduction and failure to reduction by this technique was recorded. Results: Out of 27 dislocations 22 were successfully reduced and remaining required added scapular manipulation. The mean VAS scor was 2.3±1.26 and the mean time of reduction was 17.96±1.9 minutes. Conclusion: Stimson’s method with Intraarticular Lidocaine is effective, safe, less costly and can be performed in periphery where anesthetist and monitoring facilities are not available. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6406 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 6-8